The intravenous pharmacokinetics of butorphanol and detomidine dosed in combination compared with individual dose administrations to exercised horses. Issue 2 (3rd February 2020) - Paine, Stuart W.; Bright, Jane; Scarth, James P.; Hincks, Pamela R.; Pearce, Clive M.; Hannan, Colette; Machnik, Marc; Hillyer, Lynn
Abstract: In equine and racing practice, detomidine and butorphanol are commonly used in combination for their sedative properties. The aim of the study was to produce detection times to better inform European veterinary surgeons, so that both drugs can be used appropriately under regulatory rules. Three independent groups of 7, 8 and 6 horses, respectively, were given either a single intravenous administration of butorphanol (100 µg/kg), a single intravenous administration of detomidine (10 µg/kg) or a combination of both at 25 (butorphanol) and 10 (detomidine) µg/kg. Plasma and urine concentrations of butorphanol, detomidine and 3‐hydroxydetomidine at predetermined time points were measured by liquid chromatography–tandem mass spectrometry (LC‐MS/MS). The intravenous pharmacokinetics of butorphanol dosed individually compared with co‐administration with detomidine had approximately a twofold larger clearance (646 ± 137 vs. 380 ± 86 ml hr −1  kg −1 ) but similar terminal half‐life (5.21 ± 1.56 vs. 5.43 ± 0.44 hr). Pseudo‐steady‐state urine to plasma butorphanol concentration ratios were 730 and 560, respectively. The intravenous pharmacokinetics of detomidine dosed as a single administration compared with co‐administration with butorphanol had similar clearance (3, 278 ± 1, 412 vs. 2, 519 ± 630 ml hr −1  kg −1 ) but a slightly shorter terminal half‐life (0.57 ± 0.06 vs. 0.70 ± 0.11 hr). Pseudo‐steady‐state urine to plasma detomidine concentration ratios are 4 and 8, respectively. The 3‐hydroxy metabolite of detomidine was detected for at least 35 hr in urine from both the single and co‐administrations. Detection times of 72 and 48 hr are recommended for the control of butorphanol and detomidine, respectively, in horseracing and equestrian competitions.